The effects of corporate governance attributes and code amendments on the performance of Malaysian trading and services firms - Laallam, Abdelkader; Alom, Fardous; Mohamad, Azhar (Inderscience, 2017)
This study aims to investigate the impact of corporate governance attributes and code amendments of 2012 on the performance of 162 trading and services listed firms in Bursa Malaysia. A corporate governance index score adopted from the Taylor model and formulated based on the MCCG best practices is used to measure the corporate governance attributes level. Return on assets (ROA), return on equity (ROE) and market return measurement (Tobin's Q) are used in this study. A panel data test has been conducted followed by post hoc test in order to assess the changes in firm's performance throughout the period 2010-2014. The findings show a positive significant relationship between corporate governance attributes and firm performance for accounting and market-based proxies. While the relationship between the corporate governance amendment (CGA) and accounting based firm performance proxies ROA and ROE turns out to be negatively significant with market-based firm performance proxy TQ.